2006
DOI: 10.1097/01.qai.0000191382.62070.a5
|View full text |Cite
|
Sign up to set email alerts
|

Heterosexually Transmitted HIV Infection Among African Americans in North Carolina

Abstract: Although most heterosexually transmitted HIV infection among African Americans in the South is associated with established high-risk characteristics, poverty may be an underlying determinant of these behaviors and a contributor to infection risk even in people who do not have high-risk behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
124
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(133 citation statements)
references
References 34 publications
6
124
0
3
Order By: Relevance
“…Among STD clinic attendees in St. Petersburg, Russia partner concurrency but not individual concurrency was significantly associated with diagnosed STDs. 43 Moreover, Adimora and et al, 10 in a study of heterosexually transmitted HIV among African Americans in North Carolina, found that the risk for infection with HIV among those who denied highrisk behaviors or partners was independently associated with having a sex partner who was not monogamous during the relationship with the participant. However, these studies did not specifically analyze the combined effect of both individual and partner concurrency (RSPC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among STD clinic attendees in St. Petersburg, Russia partner concurrency but not individual concurrency was significantly associated with diagnosed STDs. 43 Moreover, Adimora and et al, 10 in a study of heterosexually transmitted HIV among African Americans in North Carolina, found that the risk for infection with HIV among those who denied highrisk behaviors or partners was independently associated with having a sex partner who was not monogamous during the relationship with the participant. However, these studies did not specifically analyze the combined effect of both individual and partner concurrency (RSPC).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 In addition to these risk factors, the characteristics of sexual networks among heterosexuals, 5 specifically the pattern of sex partner concurrency (overlapping sex partnerships in the same time interval), may help to explain the heterosexual spread of HIV and other STDs in sub-Saharan Africa [6][7][8] and in high-risk urban and rural areas in the United States. [9][10][11] A high prevalence of sex partner concurrency in a population has been hypothesized to increase the number of direct or indirect sexual connections and thereby to influence the extent, rapidity, and persistence of HIV and other STD epidemics. 12 However, the theory that sex partner concurrency is a driver of heterosexual HIV epidemics has been criticized for being based on limited evidence.…”
Section: Introductionmentioning
confidence: 99%
“…43,44 Concurrent sexual partnering, defined as engaging in sex with two or more different people within the same or overlapping time period, is crucial to epidemic propagation via sexual networks [45][46][47][48] and has been shown to be independently associated with heterosexually transmitted HIV. 49 African American men are more likely than white men to report concurrent sexual relationships 50,51 and thus, concurrent partnering explains, in part, why the HIV epidemic spread has been particularly accelerated among heterosexual African Americans. 52,53 In addition to condom use, most HIV prevention interventions have focused on reducing numbers of partners and not on partner concurrency specifically, with recent reports urging such a focus.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the involved women transmit HIV/AIDS to their sexual partners (5). Drug users, comparing with nondrug users, engage in high risk behaviors (e.g.…”
Section: Introductionmentioning
confidence: 99%